Dentin remineralizasyonunda riboflavin’in etkisinin incelenmesi - Muratoğlu, Beril (My University, 2023)
Amaç: Bu in vitro çalışmanın amacı, fotoaktive Riboflavin'in demineralize dentinin remineralizasyonuna etkisinin yüzey mikrosertlik ölçümleri (SMH), X-Ray Floresans (XRF) spektroskopisi ve taramalı elektron mikroskobu (TEM) görüntülenmesi ile değerlendirmektir. Gereç ve Yöntem: Kırkbeş daimi ve 45 süt dişinden koronal dentin örnekleri rastgele altı gruba ayrıldı (n=10): Grup I: % 0,1 RF, Grup II: % 0,1 RF 30 sn Ultraviyole (UV) ışığına yakın 400 nm fotoaktivasyonu, Grup III: %0,1 RF 60 sn, Grup IV: %0,1 RF 2 dk, Grup V: pozitif kontrol (remineralizasyon solüsyonu), Grup VI: negatif kontrol (deiyonize su). Elde edilen veriler kullanılarak p<0,05 istatistiksel olarak anlamlı kabul edilerek analiz edildi. (SPSS 22.0 paket Bulgular: Süt dentin en yüksek %SMHR değeri %0,1 RF'nin 2 dk. fotoaktive edildiği grupta 31,29± 20,77 ve daimi dentinde ise; %0,1 RF 60 sn fotoaktive grupta 29,73 ± 64,37, ve aralarındaki fark istatistiksel olarak anlamlıdır (p<0,05). % 0,1 RF Ca/ P (mol) %XRF değişiminde gruplar arasında fark bulunmuştur (p<0,05). TEM görüntüsünde, süt ve daimi dentinde 2 dk fotoaktivasyon ile yüzeyde belirgin çökeltiler gözlemlendi. Sonuç: RF, dentin kolajen matriksinin mekanik özelliklerini geliştirir ve enzimatik yıkımı azaltmak için yardımcı etkileşimlerle çapraz bağlanmayı güçlendirir. Araştırmanın bulguları; demineralize dentin yüzeyine farklı fotoaktivasyon süreleri ile uygulanan %0,1 Riboflavin'in meydana getirdiği biyomodifikasyon sonucunda önemli iyileştirici etkileri gözlemlenmiştir.

Objective: The aim of this in vitro study was to evaluate the effect of photoactivated Riboflavin (RF) on the remineralization of demineralized dentin by surface microhardness measurements (SMH), X-ray fluorescence (XRF) spectroscopic examinations and Scanning Electron Microscope (SEM) analysis. Material and methods: Coronal dentin specimens obtained from 45 permanent and 45 primary teeth were randomly divided into the following six groups (n=10): Group I: 0.1% RF, Group II: 0.1% RF photoactivation 30 s near Ultraviolet (UV) light at 400 nm, Group III: 0.1% RF 60 s, Group IV: 0.1% RF 2-min, Group V: positive control (remineralization solution), Group VI: negative control (deionized water). Data were analyzed with a significance level of p<0.05 (SPSS 22.0 package programme). Results: In the primary dentin group, the highest %SMHR value was determined in the 0.1% RF 2 min group 31.29± 20.77 and in the permanent dentin group; was found in which 0.1% RF 60 seconds 29.73 ± 64.37, and the difference between them was statistically significant (p<0.05). There was a significant difference between the groups %XRF change in Ca/ P (mol) (p<0.05). SEM showed that 2-min photoactivation in primary and permanent dentin formed distinct precipitates on surface. Conclusion: RF provides through co-interactions to improve the mechanical properties of dentin collagen matrix and reduce enzymatic degradation to strengthen crosslinking. According to the findings of the research; improvement of demineralized dentin were observed as a result of the biomodification of 0.1% Riboflavin applied to the demineralized dentin surface with different photoactivation times.
The effect of photoactivated riboflavin on dentin remineralization
Keywords: dentin remineralizasyonu Riboflavin; Pedodonti; Pedodontics; remineralization of dentin; Riboflavin